Reduced Responses of Submucous Neurons from Irritable Bowel Syndrome Patients to a Cocktail Containing Histamine, Serotonin, TNFα, and Tryptase (IBS-Cocktail) - Ostertag, Daniela; Buhner, Sabine; Michel, Klaus; Pehl, Christian; Kurjak, Manfred; Götzberger, Manuela; Schulte-Frohlinde, Ewert; Frieling, Thomas; Enck, Paul; Phillip, Josef; Schemann, Michael (Frontiers in Neuroscience, 2015)
Background & Aims: Malfunctions of enteric neurons are believed to play an important role in the pathophysiology of irritable bowel syndrome (IBS). Our aim was to investigate whether neuronal activity in biopsies from IBS patients is altered in comparison to healthy controls (HC). Methods: Activity of human submucous neurons in response to electrical nerve stimulation and local application of nicotine or a mixture of histamine, serotonin, tryptase and TNF-α (IBS-cocktail) was recorded in biopsies from 17 HC and 35 IBS patients with the calcium-sensitive-dye Fluo-4 AM. The concentrations of the mediators resembeled those found in biopsy supernatants or blood. Neuronal activity in guinea-pig submucous neurons was studied with the voltage-sensitive-dye di-8-ANEPPS. Results: Activity in submucous ganglia in response to nicotine or electrical nerve stimulation was not different between HC and IBS patients (P=0.097 or P=0.448). However, the neuronal response after application of the IBS-cocktail was significantly decreased (P=0.039) independent of whether diarrhea (n=12), constipation (n=5) or bloating (n=5) was the predominant symptom. In agreement with this we found that responses of submucous ganglia conditioned by overnight incubation with IBS mucosal biopsy supernatant to spritz application of this supernatant was significantly reduced (P=0.019) when compared to incubation with HC supernatant. Conclusion: We demonstrated for the first time reduced neuronal responses in mucosal IBS biopsies to an IBS mediator cocktail. While excitability to classical stimuli of enteric neurons was comparable to HC, the activation by the IBS-cocktail was decreased. This was very likely due to desensitization to mediators constantly released by mucosal and immune cells in the gut wall of IBS patients.